PERITONSILLAR ABSCESS: CLINICAL PRESENTATION AND EFFICACY OF INCISION AND DRAINAGE UNDER LOCAL ANAESTHESIA - Khan, Muhammad Ismail; Khan, Asmatullah; Muhammad, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Peritonsillar abscess (PTA) is one of the most commonly encountered abscess in the head and neck region. The aims of this study were to list the frequency of the disease by age, sex and laterality, and to list the presentation of the disease by symptoms, signs and complications, and to determine the efficacy of incision and drainage (I&D) procedure under local anaesthesia (LA) in terms of hospital stay and recurrence. Methods: This descriptive study was conducted at the Department of Otorhinolaryngology and Head & Neck Surgery, District Headquarters Hospital, Lakki Marwat, from 1st June 2007 to 30th May 2010. Adult patients (>15 years) of both sexes with unilateral peritonsillar abscess were included sequentially. Children (15 years or less), patients with acute follicular tonsillitis or peritonsillitis and those who refused incision and drainage under LA were excluded. All patients received the same antibiotic Amoxicillin/Clavunate and underwent I&D procedure under LA. Results: Sixty patients were included in the study, 42 male and 18 female. Mean age of the patients was 30.02±9.42 (range 16-50 years). It was more on the left side (35, 58.35%). Forty-four (73.35%) patients gave an antecedent history of tonsillitis. Three (5%) patients presented with complications. Mean hospital stay was 1.55±1.00 (range 1-5 days). All patients underwent I&D with no recurrence. Interval tonsillectomy was performed in 38 selected cases after 6 weeks. Conclusion: Incision and drainage under LA still remains the gold standard procedure for peritonsillar abscess in our setup. Keywords: Peritonsillar abscess, incision and drainage, tonsillectomy